1993
DOI: 10.1128/mcb.13.6.3611
|View full text |Cite
|
Sign up to set email alerts
|

NF-HB (BSAP) is a repressor of the murine immunoglobulin heavy-chain 3' alpha enhancer at early stages of B-cell differentiation.

Abstract: We have identified a nuclear factor expressed in pro-B-, pre-B-, and B-cell lines that binds to two sites within the murine immunoglobulin heavy-chain (IgH) 3'at enhancer (3'oE). These sites were defined by oligonucleotide competition in an electrophoretic mobility shift assay (EMSA) and methylation interference footprinting. The 3'aE-binding factor is indistinguishable from NF-HB (B-lineage-specific nuclear factor that binds to the IgH gene) and the B-lineage-specific transcription factor BSAP by several

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
106
1

Year Published

1997
1997
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(108 citation statements)
references
References 46 publications
1
106
1
Order By: Relevance
“…Its action is bimodal: for example, it regulates transcription from the CD19 promoter positively, but acts negatively in the context of the IgH 3' enhancer (Singh and Birshtein, 1993;Neurath et al, 1994;Pettersson et al, 1997;Nutt et al, 1998;Maitra and Atchison, 2000). We used RNase protection mapping to assess expression levels of the PAX-5 gene in HRS cell lines relative to levels in Daudi cells (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its action is bimodal: for example, it regulates transcription from the CD19 promoter positively, but acts negatively in the context of the IgH 3' enhancer (Singh and Birshtein, 1993;Neurath et al, 1994;Pettersson et al, 1997;Nutt et al, 1998;Maitra and Atchison, 2000). We used RNase protection mapping to assess expression levels of the PAX-5 gene in HRS cell lines relative to levels in Daudi cells (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
“…Intronic and 3' enhancers of both IgH and Ig k light chain genes contain multiple elements of the E-box class, mutation of any of which significantly reduces enhancer activity (reviewed in Lieberman and Singh and Birshtein, 1993;Neurath et al, 1994). E12 and E47, that are different splicing products of the E2A gene bind these sites in B cells, although homodimers of E47 appear to be the predominant transcriptionally active form (Bain et al, 1993;Shen and Kadesch, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…BSAP (Pax5) has been implicated in the regulation of several B-cell-specific genes primarily based on the identification of BSAP-binding sites in their control regions. Putative BSAP targets are the le pro moter (Liao et al 1994) and 3' enhancers of the IgH and IgL^ loci (Singh and Birshtein 1993;Neurath et al 1994;Roque et al 1996) as well as the genes coding for the cell surface protein CD19 , the tyrosine kinase Blk (Zwollo and Desiderio 1994), the transcrip tion factor XBP-1 (Reimold et al 1996), and the surrogate light chains \5 and VpreBl (Okabe et al 1992).…”
mentioning
confidence: 99%
“…1 In vitro experiments using mobility shift assays have shown that several B-cell-specific genes contain BSAP-binding sites, including the CD19 (4, 7), CD20 (8), V pre-B , 5 (9), and blk (10) promoters, as well as IgH chain switch regions (11) and the Ig 3Ј␣ (12) enhancer. These results are somewhat in contrast with in vivo data from Pax-5 null mice (which lack BSAP) because, although pro-B-cells isolated from these mice no longer express CD19 (as would be expected), blk, V pre-B , and 5 genes are still expressed at wild-type levels (13).…”
mentioning
confidence: 99%